Implementation of a Voisin grazing system and organization of reproductive records at "La Aldea" farm - Tatés Hernández, Luis Fernando (2025)
The present investigation was carried out in the province of Carchi, canton Tulcán, Urbina parish, in the hamlet of Chapués on the “La Aldea” farm, this property is dedicated to the activity of livestock production of milk, it has an area of 20 hectares . The objective of it was: Evaluate the implementation of a Voisin Grazing System and the organization of reproductive records. For this, 7 hectares were allocated whose initial diagnosis was 7 unmanaged pastures of different sizes, where 17 cows graze with an average production of 12 liters per cow. The amount of existing grass and the reproductive parameters were unknown, since there was no reproductive record kept and no paddock management. After measuring the available dry matter (DM) using a pasture measuring plate, an amount of 1168.20 kg DM per hectare was initially obtained. The average live weight of the cows was 467 kg, with this, it was determined that, in 7 hectares, the 17 cows can remain eating for 5 days. This is given that DM consumption per cow is 3% of live weight (LW).